Integration of resistant cultivars and fungicides in the control of ramularia leaf spot and yield of cotton - Dias, Alfredo Riciere; Theodoro, Gustavo de Faria (Revista de Ciências Agroveterinárias, 2017)
Cotton is one of the main species grown in the Midwest region of Brazil and there is a high use of fungicides to control Ramularia leaf spot (RLS), an important disease caused by Ramularia areola. The objective of this study was to evaluate the integration of resistant cultivars (C) and fungicides treatments (FT) in the RLS control and yield of cotton grown in Chapadão do Sul, MS, Brazil. The experimental design consisted of randomized blocks with four replications and factorial arrangement of C (3) x FT (7). The whole plant area under the disease curve progress (AUDCP-WP) and from the lower (AUDCP-B) and upper (AUDCP-U) half of the plant were all evaluated. Likewise, cotton yield and micronaire index of the fibers were stratified. Obtained data was submitted to the F test and mean values were compared by the Scott-Knott test at 5% probability. There was a significant interaction between C and FT for AUDCP-WP, AUDCP-B and AUDCP-U but not for yield and micronaire index. Higher productivity and severity of RLS in the lower half was observed; there was no difference in productivity between cultivars; effect of C and FT in the micronaire index; and FT had no significant effect on disease severity in the resistant cultivars FMT 705 and FMT 709. These results recommend the integration of FT and C to control RLS of cotton.